Synaptic lability after experience-dependent plasticity is not mediated by calcium-permeable AMPARs - Wen, Jing A.; Barth, Alison L. (Frontiers in Molecular Neuroscience, 2012)
Activity- or experience-dependent plasticity has been associated with the trafficking of calcium-permeable AMPARs (CP-AMPARs) in a number of experimental systems. In some cases it has been shown that CP-AMPARs are only transiently present and can be removed in an activity-dependent manner. Here we test the hypothesis that the presence of CP-AMPARs confers instability onto recently potentiated synapses. Previously we have shown that altered sensory input (single-whisker experience; SWE) strengthens layer 4-2/3 excitatory synapses in mouse primary somatosensory cortex, in part by the trafficking of CP-AMPARs. Both in vivo and in vitro, this potentiation is labile, and can be depressed by NMDAR-activation. In the present study, the role of CP-AMPARs in conferring this synaptic instability after in vivo potentiation was evaluated. We develop an assay to depress the strength of individual layer 4-2/3 excitatory synapses after SWE, using a strontium (Sr++)-replaced ACSF solution (Sr-depression). This method allows disambiguation of changes in quantal amplitude (a post-synaptic measure) from changes in event frequency (typically a presynaptic phenomenon). Presynaptic stimulation paired with postsynaptic depolarization in Sr++ lead to a rapid and significant reduction in EPSC amplitude with no change in event frequency. Sr-depression at recently potentiated synapses required NMDARs, but could still occur when CP-AMPARs were not present. As a further dissociation between the presence of CP-AMPARs and Sr-depression, CP-AMPARs could be detected in some cells from control, whisker intact animals, although Sr-depression was never observed. Taken together, our findings suggest that CP-AMPARs are neither sufficient nor necessary for experience-dependent synaptic plasticity in somatosensory neocortex.